Stress-Induced Cellular Clearance Is Mediated by the SNARE Protein ykt6 and Disrupted by α-Synuclein - Cuddy, Leah K.; Wani, Willayat Y.; Morella, Martino L.; Pitcairn, Caleb; Tsutsumi, Kotaro; Fredriksen, Kristina; Justman, Craig J.; Grammatopoulos, Tom N.; Belur, Nandkishore R.; Zunke, Friederike; Subramanian, Aarthi; Affaneh, Amira; et al. (Neuron, 2019)
Age-related neurodegenerative disorders are characterized by a slow, persistent accumulation of aggregated proteins. Although cells can elicit physiological responses to enhance cellular clearance and counteract accumulation, it is unclear how pathogenic proteins evade this process in disease. We find that Parkinson's disease α-synuclein perturbs the physiological response to lysosomal stress by impeding the SNARE protein ykt6. Cytosolic ykt6 is normally autoinhibited by a unique farnesyl-mediated regulatory mechanism; however, during lysosomal stress, it activates and redistributes into membranes to preferentially promote hydrolase trafficking and enhance cellular clearance. α-Synuclein aberrantly binds and deactivates ykt6 in patient-derived neurons, thereby disabling the lysosomal stress response and facilitating protein accumulation. Activating ykt6 by small-molecule farnesyltransferase inhibitors restores lysosomal activity and reduces α-synuclein in patient-derived neurons and mice. Our findings indicate that α-synuclein creates a permissive environment for aggregate persistence by inhibiting regulated cellular clearance and provide a therapeutic strategy to restore protein homeostasis by harnessing SNARE activity.
CRIS-Team Scopus Importer:2020-10-21
Keywords: induced pluripotent stem cells; lysosomal storage disease; lysosomal stress; Parkinson's disease; protein aggregation; proteomic stress; synucleinopathy